A systematic literature review of bamboo as reinforcement in concrete - Ipsitaa Priyadarsini Das; Pradeep G. Kini; Shreelaxmi Prashant (Discover Sustainability)
Abstract The building industry is a major contributor to global greenhouse gas emissions, particularly CO2, accounting for about 30%. With an expected world population growth of over 2 billion by 2030, the demand for 300 million new housing units will escalate the consumption of non-renewable building materials. Within industrialized nations, the share of primary energy consumption by the construction sector hovers around 40%, while energy-related CO2 emissions account for 36% of the total. Material production and construction processes significantly amplify greenhouse gas emissions, raising their atmospheric concentrations. Conventional materials like cement, steel, and glass are major CO2 emitters, posing challenges to the Paris Agreement’s goals of limiting temperature rise and achieving zero emissions by 2050. To meet these goals and align with Sustainable Development Goal 9, adopting alternative materials is crucial. Bamboo, recognized for its durability, renewability, and eco-friendliness, is emerging as a viable substitute for steel in reinforced concrete structures. This study analyzes the feasibility of bamboo as a sustainable alternative to steel reinforcement, focusing on its mechanical properties and applications in construction. The review, conducted using the PRISMA 2020 method, screened 467 papers, narrowing down to 48 research papers and 2 Indian Standard codes. Findings show that Bambusa balcoa, Bambusa vulgaris, Dendrocalmus asper, and Bambusa bamboo are the most commonly examined species, demonstrating average tensile strength of 118.578 MPa and modulus of elasticity of 15.529 GPa. Bamboo reinforcement also offers significant cost savings (approximately 36.78%) and lower carbon emissions, making it a promising eco-friendly alternative to steel in concrete structures. Clinical trial registration: Not applicable.